PENENTUAN KONSUMSI OKSIGEN (VO2) MAKSIMAL DAN PENGEMBANGAN PREDIKSI PERSAMAAN REGRESI VO2 TERPAPAR TEMPERATUR - , ANNISA PURBASARI; , Nur Aini Masruroh, S.T., M.Sc., Ph.D., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
There is a close relationship between the application of ergonomics and exercise physiology which can be aimed to achieve outstanding athlete and maximal productivity. The High-performance of athletes may be affected by a balanced relationship among the load factor, physical capacity, and environment. The purpose of this study was to determine maximal oxygen consumption (VO2max), determine the effect of environmental temperature variation of the maximal VO2 and develop prediction equations of oxygen consumption (VO2) which exposed to temperatures. One approach to determine the physical performance of athletes is through the measurement of VO2max and VO2. The study is divided into four stages: phase 1 to determine VO2max, phase 2 to develop VO2 equation, phase 3 and 4 to validate the given data validation into two treatments in temperature at WBGT 25,5±1,7oC and. Phase 1, phase 2 and phase 3 are to conduct activities in treadmill jogging, while the phase 4 is to conduct manual material handling (MMH) activities. The involved subjects to determine VO2max and develop VO2 equation are 10 men, aged 18-25 years and clothed tropical wear 0,3 Clo. The test determination of maximal VO2max was done with the protocol and equation which developed with sub-maximal test protocol. VO2 equation was developed based on the relationship between the variables of heart rate, age, height, weight and environmental temperature. Validation is done by simulating jogging and MMH. Validation for performance testing of the equation is by 5 men aged 19-21 years. Statistical analysis was performed to test normality, multiple linear regression analysis, and test of pairedsamples t-test. These results indicated that VO2max at WBGT 25,5±1,7oC was 2,466±0,419 L/min and VO2max values at WBGT 32,9±1,7oC was 2,466 ± 0,327L/min. Temperature variation on WBGT 25,5±1,7oC showed no significant difference in VO2max with temperature variations on WBGT 32,9±1,7oC. From the research results is obtained three equations. The first equation has R2 with value of 0,922, adjusted R2 value of 91,7% which can be explained by two variables VO2 including heart rate, weight and value of the Standard Error of the Estimate (SEE) of 0,198. The second equation has R2 value of 0,944, adjusted R2 value of 94%, VO2 variation is explained by two variables included heart rate and Wet-Bulb Globe Temperature (WBGT), while SEE was 0,165. For the third equation, it has R2 value of 0,917 with an adjusted R2 of 91.3%, this means that the equation resulting from the variation of the three variables: heart rate, body weight and WBGT can be used to explain the variation in VO2 with a SEE value of 0,199.